Detection of Virus-Related Sequences Associated With Potential Etiologies of Hepatitis in Liver Tissue Samples From Rats, Mice, Shrews, and Bats - He, Wenqiao; Gao, Yuhan; Wen, Yuqi; Ke, Xuemei; Ou, Zejin; Li, Yongzhi; He, Huan; Chen, Qing (Frontiers in Microbiology, 2021)
Hepatitis is a major global health concern. However, the etiology of 10-20% hepatitis cases remains unclear. Some hepatitis-associated viruses, like the hepatitis E virus, are zoonotic pathogens. Rats, shrews, and bats are reservoirs for many zoonotic pathogens. Therefore, understanding the virome in the liver of these animals is important for the investigation of the etiologies of hepatitis and monitoring the emerging zoonotic viruses. In this study, viral metagenomics and PCR methods were used to investigate viral communities in rats, mice, house shrews, and bats livers. Viral metagenomic analysis showed a diverse set of sequences in liver samples, comprising: sequences related to herpesviruses, orthomyxoviruses, anelloviruses, hepeviruses, hepadnaviruses, flaviviruses, parvoviruses, and picornaviruses. Using PCR methods, we first detected hepatovirus sequences in Hipposideros larvatus (3.85%). We also reported the first detection of Zika virus-related sequences in rats and house shrews. Sequences related to influenza A virus and herpesviruses were detected in liver. Higher detection rates of pegivirus sequences were found in liver tissue and serum samples from rats (7.85% and 15.79%, respectively) than from house shrews. Torque teno virus sequences had higher detection rates in the serum samples of rats and house shrews (52.72% and 5.26%, respectively) than in the liver. Near-full length genomes of pegivirus and torque teno virus were amplified. This study is the first to compare the viral communities in the liver of bats, rats, mice, and house shrews. Its findings expand our understanding of the virome in the liver of these animals and provide an insight into hepatitis-related viruses.